Integrated frozen concentrated dalandan juice extract and powdered pectin plant - Domingo, Lorielyn A.; Lansangan, Marco M.; Nahoman, Kristina M.
The main products of the integrated plant are frozen concentrated dalandan extract and powdered pectin. The by-product generated from the drying of dalandan peels in the production of pectin powder is sold as cattle feed. The primary raw material used in the integrated production of dalandan extract and pectin is the whole dalandan fruit. The fruits are ordered from the citrus farm cooperative in Malabing Valley, located in Kasibu, Nueva Vizcaya. The other raw material used are deionized water, sugar, hydrochloric acid, and isopropyl alcohol. The plant will be located in Nueva Vizcaya where most of the raw materials are obtained.Concentrated dalandan extract is produced using the FMC citrus juice extractor. Dalandan juice will undergo several process including pasteurization and freezing to obtain concentrated dalandan extract. The concentrated dalandan extract produced is canned or packed in 1 and 10 liter-polyethylene bags which are then sent through a blast freezer for storage. Frozen concentrated dalandan extract is mainly used as a raw material in the production of single-strength dalandan juice and acts as flavor additive in soft drinks and other carbonated drinks.The waste peels discarded from the dalandan extract production will be the primary raw material used in the production of pectin. Pectin is produced by extraction using hydrochloric acid at 90°C and precipitation using isopropyl alcohol. The wet pectin will be dried in tray dryers at 60°C. The powdered pectin produced is packed in polyethylene bags at 5, 25, and 50 kilograms. About 98% of pectin is used in food applications and 2% in other non-food industries. Pectin is basically used in thickener and stabilizer of the product shown in Table 1